TRADISI SASI DI RAJA AMPAT PAPUA - Febyarandika S., Shiffa; Chafid, Muhammad abdul (Fakultas Ilmu Budaya Universitas Diponegoro, 2016)
Raja Ampat is one of the districts in Papua which has the potential of the best biodiversity in the world. The conservation system in Raja Ampat is called sasi, which is a local tradition to close the fishing season at a certain time. The tradition is important for the fish to reproduce, so that natural resources can be sustainable in Raja Ampat. Sasi is based on the absorption ratio of fish catch, and it is devided into intended sasi and deliberate sasi. Sasi can be conditional or unconditional. Sasi is beneficial because local tradition can be maintained, while adding the catch of fishermen and increasing revenues for tourism